Effects of an Interdisciplinary Course on Pre-Service Primary Teachers' Content Knowledge and Academic Self-Concepts in Science and Technology-A Quantitative Longitudinal Study - Melanie Marita Beudels; Karsten Damerau; Angelika Preisfeld (MDPI AG, 2021)
Primary school teachers need adequate professional knowledge and motivational orientations to qualify scientifically and technologically literate students. Previous studies have focused on the impact of coursework on (pre-service) primary teachers' content knowledge, rather than on the development of academic self-concepts. In addition, the influence of the course format and the major field of study has not been investigated much to this date. Thus, this study examines the effects of an interdisciplinary course on pre-service primary teachers' content knowledge and academic self-concepts in science and technology using a quasi-experimental, quantitative, pre-post-follow-up design (n = 202). Whilst no significant changes in knowledge were revealed for the baseline group not participating in the course, significant short-term and long-term cognitive gains were found for the experimental group. Biology-, chemistry-, physics- and technology-related self-concepts increased significantly when participating in the course. The results also indicate that the course format and major field of study can have an impact on the development of pre-service teachers' professional knowledge. Regarding the development of academic self-concepts in the experimental group, it can be assumed that both the weekly and block course format are beneficial for heterogeneous learner groups consisting of pre-service teachers with different major fields of study.